Chronic wound repair and healing in older adults: Current status and future research. Issue 1 (13th February 2015) - Gould, Lisa; Abadir, Peter; Brem, Harold; Carter, Marissa; Conner‐Kerr, Teresa; Davidson, Jeff; DiPietro, Luisa; Falanga, Vincent; Fife, Caroline; Gardner, Sue; Grice, Elizabeth; Harmon, John; et al.
Abstract The incidence of chronic wounds is increased among older adults, and the impact of chronic wounds on quality of life is particularly profound in this population. It is well established that wound healing slows with age. However, the basic biology underlying chronic wounds and the influence of age‐associated changes on wound healing are poorly understood. Most studies have used in vitro approaches and various animal models, but observed changes translate poorly to human healing conditions. The impact of age and accompanying multi‐morbidity on the effectiveness of existing and emerging treatment approaches for chronic wounds is also unknown, and older adults tend to be excluded from randomized clinical trials. Poorly defined outcomes and variables, lack of standardization in data collection, and variations in the definition, measurement, and treatment of wounds also hamper clinical studies. The Association of Specialty Professors, in conjunction with the National Institute on Aging and the Wound Healing Society, held a workshop, summarized in this paper, to explore the current state of knowledge and research challenges, engage investigators across disciplines, and identify key research questions to guide future study of age‐associated changes in chronic wound healing.